An inconvenient truth (DVD) - Gore, Albert 1948-.; Guggenheim, Davis; David, Laurie; Bender, Lawrence; Burns, Scott Z.; Skoll, Jeff.; Chilcott, Leslie; Richman, Bob.; Cassidy, Jay.; Swietlik, Dan.; Brook, Michael musician; Participant Productions; et al. (Hollywood, Calif. Paramount, 2006)
Former Vice President Al Gore explains the facts of global warming, presents arguments that the dangers of global warning have reached the level of crisis, and addresses the efforts of certain interests to discredit the anti-global warming cause. Between lecture segments, Gore discusses his personal commitment to the environment, sharing anecdotes from his experiences.
Special features: Commentary with director Davis Guggenheim -- Commentary with producers Laurie David, Lawrence Bender, Scott Z. Burns and Leslie Chilcott -- An update with former Vice-President Al Gore.
Documentary.
Subtitle on disc label: A global warning.
Released theatrically in 2006; program content: c2005.
"34808 "--Container.
"11111004689"--Container.
Cinematographers, Bob Richman, Davis Guggenheim ; editors, Jay Lash Cassidy, Dan Swietlik ; music, Michael Brook.
Keywords: Gore, Albert -- 1948-.; Global warming; Global warming -- Government policy -- United States; Greenhouse effect, Atmospheric; Greenhouse effect, Atmospheric -- Government policy -- United States; Environmental policy -- United States; Environmental protection -- United States; Human ecology; Risk perception